Obstetric and perinatal outcome of elderly mothers aged 35 years and above: a comparative study - Ramachandran, Nirmala; Sethuraman, Dhivya; Nachimuthu, Vanathi; Natrajan, Thamizhselvi (International Journal of Research in Medical Sciences, 2017)
Background:Across the world, there is a rising trend among women towards delaying pregnancy and child birth. The wide educational and career choices available currently encourage women to pursue their professional goals relentlessly and many opt to delay pregnancy. Easy access to the wide range of modern contraceptive methods has enabled them to achieve better control of fertility. Methods: The study conducted in Chennai Medical College and Research Centre, Trichy over a period of 18 months compared pregnancy related complications, maternal and perinatal outcomes in elderly women, with non-elderly women as controls. Forty two elderly gravidae were compared with 50 non-elderly gravidae. Results: The mean age of women in study group was 37.1 and 27.6 in the control group. 14.3% in the study group of patients had assisted conception whereas all of patients in the control group conceived spontaneously. There were 4 (9.5%) miscarriages in the study group and none in the control group. The incidence of pre-gestational diabetes, gestational diabetes and preeclampsia was found to be higher in the study group and this was statistically significant (P Value <0.0001). Conclusion:This study analyzing the effect of advanced maternal age on pregnancy has shown favourable maternal and perinatal outcomes. The study showed a significant difference in the incidence of pre-gestational diabetes, gestational diabetes, preeclampsia, miscarriage, antepartum hemorrhage, induction of labour, instrumental deliveries and caesarean section rates in elderly gravidae. But the risk of aneuploidy, malpresentations, placenta previa and prolonged labour were not found to be high. The incidence of low APGAR score was high in the study group, but it was attributable to specific causes like placental abruption. There were no perinatal deaths in both groups.